Effect of adding lemon peels oils to gelatin edible films on some quality characteristics of storage chilled chicken breast meat - Qurabi, Nesreen Abdulqader; Azizieh, Abdulhakim Fahed; Merai, Abdulwahab Sino (Journal of agricultural, environmental and veterinary sciences, 2021)
The aim of this investigation is to specific shelf life of storage chilled chicken breast meat by filling it with gelatin-sodium alginate edible films which contain lemon peels essential oil (LPO) at various final concentrations. Lemon peels essential oil was prepared by steam distilling, and gelatin-sodium alginate edible films were prepared, and LPO was added by the following percentages (0, 0.5, 1, 1.5, 2 %). These groups were packaged in gelatin-sodium alginate edible films, then preserved at (4±1° C) for 18 days and examined after 0, 3, 7, 11, 14 and 18 days of refrigeration for total count of bacteria, freshness and chemical properties. Freshness analyses included determination of pH value and thiobarbituric acid TBA. Chemical analyses included determination of moisture, ash, fat, and protein content. The samples treated by gelatin-sodium alginate edible films with 2 % LPO had the best quality characteristics during the chilled storage period, thereby samples of chicken breast meat had saved of quality characteristics for 14 days.